THE EFFECT OF INTRADIALYTIC EXERCISE ON INTRADIALYTIC HYPERTENSION IN CHRONIC KIDNEY FAILURE PATIENTS UNDERGOING HEMODIALYSIS AT RSUD DR. ADJIDARMO RANGKASBITUNG - Siti Sindi; Bangun Wijonarko; Andi Sudrajat (Journal of Noncommunicable Diseases Prevention and Control, 2026)
Chronic kidney disease (CKD) results in the failure to excrete body waste. Hemodialysis, the primary treatment, often triggers intradialytic hypertension. One non-pharmacological solution to manage this condition is intradialytic exercise. To determine the effect of intradialytic exercise on intradialytic hypertension in chronic renal failure patients undergoing hemodialysis. Quantitative research with Quasi Experimental design (Pretest-Posttest with Control Group).  In the intervention group, there was a significant decrease in blood pressure after intradialytic exercise. The mean systolic blood pressure decreased from 159.55 mmHg to 145.73 mmHg, and diastolic blood pressure from 97.82 mmHg to 83.27 mmHg with a p value = 0.000 (<0.05). Meanwhile, the control group had a mean pre-systolic blood pressure of 168.45 mmHg and pre-diastolic blood pressure of 91.64 mmHg, while post-systolic blood pressure was 169.36 mmHg and post-diastolic blood pressure was 96.82 mmHg with a p value = >0.05. Intradialytic exercise has been proven to be effective in lowering blood pressure in chronic kidney failure patients undergoing hemodialysis in the Hemodialysis Room at RSUD Dr. Adjidarmo Rangkasbitung.